2021
DOI: 10.1021/acs.jpclett.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Onset of Nitric Acid Dissociation in Cs+·(HNO3)(H2O)n=0–11 Clusters at 20 K

Abstract: We report the water-mediated charge separation of nitric acid upon incorporation into size-selected Cs + •(HNO 3 )(H 2 O) n=0−11 clusters at 20 K. Dramatic spectral changes are observed in the n = 7−9 range that are traced to the formation of many isomeric structures associated with intermediate transfer of the acidic proton to the water network. This transfer is complete by n = 10, which exhibits much simpler vibrational band patterns consistent with those expected for a tricoordinated hydronium ion (the Eige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…This mode has been probed using vibrational spectroscopies, because it reports on the local structure of the hydrogen-bond network in water; when water is strongly (weakly) hydrogen-bonded, the frequency of the bending mode is blue-shifted (red-shifted). , Probing the bending mode of water has several advantages over probing the O–H stretch mode. Whereas the O–H stretch mode of water cannot be spectrally distinguished from other molecules containing OH-groups, the H–O–H water bending mode is specific to water. Also, the vibrational coupling between bending modes has a limited impact on its spectral response, , in sharp contrast to the O–H stretch mode. , Furthermore, understanding the bending mode is essential to unveil the vibrational energy transfer from the O–H stretch mode of water and the amide mode of proteins to the local heat, because the bending mode is believed to be an essential intermediate step to receive excess vibrational energy and release it to the local heat. , …”
Section: Introductionmentioning
confidence: 99%
“…This mode has been probed using vibrational spectroscopies, because it reports on the local structure of the hydrogen-bond network in water; when water is strongly (weakly) hydrogen-bonded, the frequency of the bending mode is blue-shifted (red-shifted). , Probing the bending mode of water has several advantages over probing the O–H stretch mode. Whereas the O–H stretch mode of water cannot be spectrally distinguished from other molecules containing OH-groups, the H–O–H water bending mode is specific to water. Also, the vibrational coupling between bending modes has a limited impact on its spectral response, , in sharp contrast to the O–H stretch mode. , Furthermore, understanding the bending mode is essential to unveil the vibrational energy transfer from the O–H stretch mode of water and the amide mode of proteins to the local heat, because the bending mode is believed to be an essential intermediate step to receive excess vibrational energy and release it to the local heat. , …”
Section: Introductionmentioning
confidence: 99%
“…This metric was explored in detail, for example, in a study that illustrated how the frequency of the shared proton in a series of proton-bound dimers B 1 :H + :B 2 depends on the proton affinities of the Bronsted bases B 1 and B 2 . In the case of the Cs + ·(HNO 3 )­(H 2 O) n system, clusters formed by electrospray ionization can occur with one water molecule attached to the acid, while the remaining waters reside in the first hydration shell of the ion. , For the n = 1 system, the key bands and structure of this ternary complex are indicated in Figure b, where a red shift of 867 cm –1 is observed for ν OH a–w relative to the value in the bare ion Cs + ·(HNO 3 ) (blue, ν OH a in Figure a and navy blue, ν OH a–w in Figure b) . To put this in context, the addition of a water molecule to HNO 3 in carbon tetrachloride causes the OH stretch to red-shift relative to the solvated acid OH stretch ( CC l 4 ν OH a ) by only ∼ 385 cm –1 .…”
Section: Introductionmentioning
confidence: 99%
“…The unusual behavior of HNO 3 at the air–water interface is currently under investigation with a variety of theoretical and experimental methods. Specifically, it has been proposed that this strong acid (under typical aqueous conditions) is only partially ionized near the water surface where the counterions are less efficiently solvated. ,, Understanding the nature of aqueous HNO 3 in pure water, as well as in the presence of electrolytes, has motivated several theoretical and experimental efforts designed to establish how its p K a depends on the local environment. These involve the elucidation of HNO 3 behavior at the air–water interface, as well as in well-defined cluster systems (e.g., Cs + ·(HNO 3 )­(H 2 O) n =0–11 ). ,− The advantage of the cluster regime is that electronic structure calculations can be applied to harvest the structural information encoded in experimental vibrational band patterns obtained with size-selective, cryogenic photofragmentation mass spectrometry . Using this approach, for example, Mitra et al recently observed the cluster-size-dependent onset of the solvent-separated, NO 3 – /H 3 O + ion pair in the ∼20 K Cs + ·(HNO 3 )­(H 2 O) n system at n ∼ 10. Calculations revealed the critical role played by the proximal Cs + ion to stabilize the incipient NO 3 – conjugate base in a water network-mediated, Cs + /NO 3 – /H 3 O + salt bridge arrangement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrational band patterns displayed by size-selected M ± ·(H 2 O) n cluster ions arising from the molecular ions, M ± , as well as those arising from the water molecules, encode how the local interactions are modulated by the shapes of the water networks. , At a qualitative level, molecular ions can induce an electric dipole moment in the first hydration shell arising from partial orientation of the water molecules, which in turn imposes a solvent “reaction field” , on the ion. This solvent electric field can then distort the embedded ion by both electronic and structural contributions to its polarizability .…”
Section: Introductionmentioning
confidence: 99%